Lower incidence of acute GVHD is associated with the rapid recovery of CD4+CD25+CD45RA+ regulatory T cells in patients who received haploidentical allografts from NIMA-mismatched donors: A retrospective (development) and prospective (validation) cohort-based study. (1st December 2016) - Wang, Yu; Zhao, Xiang-Yu; Xu, Lan-Ping; Zhang, Xiao-Hui; Han, Wei; Chen, Huan; Wang, Feng-Rong; Mo, Xiao-Dong; Zhang, Yuan-Yuan; Zhao, Xiao-Su; Y., Kong; Liua, Kai-Yan; et al.
ABSTRACT: To investigate the effects of non-inherited maternal antigen (NIMA) on clinical outcomes and immune recovery, especially of regulatory T cells (Tregs), in patients who underwent unmanipulated haploidentical transplantation. A retrospective cohort (n = 57) and a prospective cohort (n = 88) were included. All patients received haploidentical allografts from sibling donors. Reconstitution of immune subsets, including Tregs, was determined using multicolor flow cytometry. In the retrospective cohort, the cumulative incidence of grades II–IV acute GVHD in patients with NIMA-mismatched donors was significantly lower than that of cases with NIPA-mismatched donors (14.8% vs. 43.30%, p = 0.018). Patients with higher percentages of CD4 + CD25 + CD45RA + T cells (naive Tregs) within CD4 + T cells recovered on day 30 (≥1.55%) experienced a significantly lower incidence of grades II–IV acute GVHD than that of cases with lower percentages of naive Tregs (<1.55%) (13.8% vs. 46.4%, p = 0.010). Multivariate analysis showed that NIMA mismatch and the percentages of naive Tregs were associated with the incidence of grades II–IV acute GVHD [ p = 0.050, and 0.031, respectively]. In the prospective cohort, the association of NIMA mismatch [HR = 0.365, 95% CI, 0.169–0.786, p = 0.010] or higher percentages of naive Tregs recovered on day 30 (≥1.55%) [HR = 0.114, 95% CI, 0.027–0.479, p = 0.003] with a lower cumulative incidence of grades II–IV acute GVHD was further demonstrated. No effects of NIMA mismatch on chronic GVHD, transplant-related mortality, relapse, disease-free survival, or overall survival were found. Our results confirmed the role of NIMA mismatch in acute GVHD and provided the first demonstration, based on clinical data, that recovered Tregs may be involved in the effects of NIMA on acute GVHD in a haploidentical transplant setting.